Pengaruh Motivasi Kerja Budaya Organisasi Dan Kepuasan Kerja Terhadap Kinerja Guru Sekolah Dasar Di Kecamatan Malunda Provinsi Sulawesi Barat - Sahari; Yusram Adi; Andi Irwan (Jurnal Online Manajemen ELPEI, 2023)
This study aims to examine work motivation, organizational culture and job satisfaction on teacher performance. The approach used in this study is a quantitative approach, the sample in this study is elementary school teachers in the Maluku district, West Sulawesi, totaling 100 people. The results of the T test of this study indicate that the variables Work Motivation, Organizational Culture, and Job Satisfaction have a positive and significant effect on teacher performance and the results of the F test indicate that the variables work motivation, organizational culture, and job satisfaction have a positive and significant effect on teacher performance together.